Makna Tarian Sufi Perspektif Komunitas Tari Sufi Dervishe Pekalongan - Slamet Nugroho (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Spiritual dance has a deep meaning. One of the Sufi dancers from Dervishe Pekalongan revealed that there are many meanings contained in the dance, one of which is love. The dancer must present love in his heart and in every breath only for Allah, from feelings of love it is hoped that all Sufi dancers can accept and live all life in the world with great love for Allah. Based on this, it is studied about the Meaning of Sufi Dance from the Perspective of the Sufi Dance Community Dervishe Pekalongan. This research is a type of qualitative research. The main target of the research is how to implement the meaning of Sufi dance in the daily life of the Sufi Dance community of Dervishe Pekalongan. The results show that in Sufi dances there are attributes used by the dancers and the movements they perform, including: Sikke, tennur, black belt, and Khuff. The meaning of Sufi dance in the perspective of the Sufi dance community of Dervishe Pekalongan consists of two descriptions, namely the meaning of the attributes and the meaning of the movement.